Simultaneous injection effective mixing flow analysis of urinary albumin using dye-binding reaction - Ratanawimarnwong N. (2014)
A new four-channel simultaneous injection effective mixing flow analysis (SIEMA) system has been assembled for the determination of urinary albumin. The SIEMA system consisted of a syringe pump, two 5-way cross connectors, four holding coils, five 3-way solenoid valves, a 50-cm long mixing coil and a spectrophotometer. Tetrabromophenol blue anion (TBPB) in Triton X-100 micelle reacted with albumin at pH 3.2 to form a blue ion complex with a λ max 625 nm. TBPB, Triton X-100, acetate buffer and albumin standard solutions were aspirated into four individual holding coils by a syringe pump and then the aspirated zones were simultaneously pushed in the reverse direction to the detector flow cell. Baseline drift, due to adsorption of TBPB-albumin complex on the wall of the hydrophobic PTFE tubing, was minimized by aspiration of Triton X-100 and acetate buffer solutions between samples. The calibration graph was linear in the range of 10-50 μg/mL and the detection limit for albumin (3σ) was 0.53 μg/mL. The RSD (n = 11) at 30 μg/mL was 1.35%. The sample throughput was 37/h. With a 10-fold dilution, interference from urine matrix was removed. The proposed method has advantages in terms of simple automation operation and short analysis time. © 2012 Elsevier B.V. All rights reserved.